Effect of oxygenation with micronanobubbles on water quality and production of “trout” Oncorhynchus mykiss - Pizarro Ramos, Royer (2022)
The experimental research was developed in the town of Circarmarca, Ayacucho-Peru, to evaluate the effect of MNB on water quality and the growth of Oncorhynchus mykiss “rainbow trout”.